Kebijakan Bea Perolehan Hak atas Tanah dan Bangunan Terutang dalam Peraturan Menteri ATR/BPN Nomor 6 Tahun 2018 Tentang Pendaftaran Tanah Sistematis Lengkap Ditinjau dari Konsep Freies Ermessen - Rusli M. Mau; Akbar Sabto; Masdin; Imran (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
Permen ATR/BPN Number 6 of 2018 concerning PTSL regulates the BPHTB owed on PTSL Yield Certificates. This provision conflicts with Law no. 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments so the author hypothesizes that the ATR/BPN Minister issued these provisions based on the Freies Ermessen concept. The problem posed is whether it is true that the BPHTB provisions owed by Permen ATR/BPN No. 6 of 2018 adheres to the Freies Ermessen concept, secondly how ATR/BPN officials as PTSL executors respond to the settlement of these norms, this problem is discussed with a regulatory and conceptual approach, this paper concludes correctly that BPHTB is owed by Permen ATR/BPN No. 6 of 2018 adheres to the concept of freies ermessen, and ATR/BPN officials can implement the provisions of the BPHTB owed according to Permen ATR/BPN No. 6 of 2018 based on the principle of presumption of validity